Ageing Russia, possibilities of substantial revolutionary changes and youth-related problems - Rukavishnikov Vladimir (Međunarodni Problemi, 2013)
The paper deals with the problem of demographic ageing in Russia, some forecasts of the possible substantial revolutionary changes, and present youth activities. The author discusses results of the recent study conducted by the Department of Elite Studies of the Institute of Sociology of the Russian Academy of Sciences. Data of this survey and personal observations of the author confirm the opinion about the absence of such changes in contemporary Russia, despite the involvement of a portion of youth in protest rallies which occurred in winter 2012/13 in the capital and big cities which was reduce to the slogan “For honest elections!” The issue of youth violence was slightly tackled.